2011
DOI: 10.1029/2009jc005944
|View full text |Cite
|
Sign up to set email alerts
|

Forcing of oceanic heat anomalies by air-sea interactions in the Nordic Seas area

Abstract: [1] Hydrographic data and atmospheric reanalysis from 1982 to 2005 are used to show a strong link of the Atlantic water temperature (AWT) anomalies observed in the transition zone between the Norwegian Atlantic current and the West Spitsbergen current in summer to the surface heat flux (SHF) anomalies observed over the Barents Sea open water in the preceding late winter. A mechanism proposed for this link is formation of ocean temperature anomalies in a deep mixed layer and their subsequent westward export by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 53 publications
12
47
0
Order By: Relevance
“…This lends support to the idea that it is the gradient at the interface of the Siberian high that is key in determining the sea ice evolution (discussed further below) and that this regional variability is not necessarily well represented by large-scale metrics such as the Arctic Oscillation. This result is consistent with previous studies that have suggested that local SLP gradients control interannual Barents Sea ice variability (Sorteberg and Kvingedal 2006;Schlichtholz and Houssais 2011;Inoue et al 2012;Herbaut et al 2015) and with studies that have suggested a combined role of both the Aleutian low and Siberian high in driving ice-ocean conditions in the Sea of Okhotsk (e.g., Parkinson 1990;Tachibana et al 1996;Nakanowatari et al 2015, among others).…”
Section: Fig 2 As Insupporting
confidence: 82%
“…This lends support to the idea that it is the gradient at the interface of the Siberian high that is key in determining the sea ice evolution (discussed further below) and that this regional variability is not necessarily well represented by large-scale metrics such as the Arctic Oscillation. This result is consistent with previous studies that have suggested that local SLP gradients control interannual Barents Sea ice variability (Sorteberg and Kvingedal 2006;Schlichtholz and Houssais 2011;Inoue et al 2012;Herbaut et al 2015) and with studies that have suggested a combined role of both the Aleutian low and Siberian high in driving ice-ocean conditions in the Sea of Okhotsk (e.g., Parkinson 1990;Tachibana et al 1996;Nakanowatari et al 2015, among others).…”
Section: Fig 2 As Insupporting
confidence: 82%
“…This especially explains the increased flow in the offshore branch that is more closely related to the gyre circulation than the flow near the West Spitsbergen shelf break and causes an increase in recirculation in central Fram Strait in winter (de Steur et al 2014). Similarly, the airsea heat fluxes over the Nordic Seas are much stronger in winter than in summer (Simonsen and Haugan 1996;Schlichtholz and Houssais 2011), and this is the reason for the hydrographic structure of the Atlantic Water (AW) in the WSC in the different seasons. The weak stratification in winter is a result of the intense winter cooling that the water has been subjected to in the Nordic Seas.…”
Section: B Discussionmentioning
confidence: 93%
“…The NAO not only controls large-scale atmospheric conditions, but it also influences oceanic variability. In particular, our summer AWT index is significantly linked to the NAO index of previous winters (Schlichtholz and Houssais 2011). However, it is not correlated with the NAO index of the following winter (r = −0.06).…”
Section: Link To the North Atlantic Oscillationmentioning
confidence: 88%
“…Oceanic heat variability is represented by the summer (JJAS) time series of AWT constructed by Schlichtholz and Houssais (2011) (Boyer et al 2006). The temperature data were averaged over the Atlantic water core (100-300 m) in the BSO area (13-17 • E, 70-76 • N; magenta box in Fig.…”
Section: Ocanic Data and Composite Analysismentioning
confidence: 99%
See 1 more Smart Citation